Emerging Evidence of IgG4-Related Disease in Pericarditis: A Systematic Review - Dilan Hikmat; Saman Al Barznji; Adolfo Martinez; Akhil Gaderaju; Mohammed Alaa Raslan; Mohammad Almasri; Karam Ghazal-Aswad; Ghasaq Saleh; Rohan Kumar; Maitri Shah (Barw Medical Journal, 2025)
AbstractIntroductionImmunoglobulin G4-related disease (IgG4-RD) is a recently identified immune-mediated condition that is debilitating and often overlooked. While IgG4-RD has been reported in several organs, this study reviews cases where IgG4-RD caused pericarditis.MethodsA systematic search was conducted from inception until March 1, 2025. All age groups and both sexes with confirmed pericarditis were included, along with the following inclusion criteria: 1) Patients with pericardial biopsy showing IgG4/IgG ratio of >40%. 2) Patients with pericardial biopsy revealing IgG4/HPF of >10. 3) Patients who had confirmed IgG4-RD from other organ biopsies through IgG4 staining, or diagnostic imaging suggestive of IgG4-RD, or pericardial biopsy with classic IgG4-RD histopathologic patterns, with elevated serum IgG4 levels, provided no other diagnosis was more likely.ResultsA total of 50 patients were included, with a mean age of 64.86±15.79 years. There were 36 (72%) males. The most common presenting symptom was dyspnea in 27 (54%) patients. Different pericardial involvements were reported, including pericardial thickening 37 (74%), constrictive pericarditis 28 (56%), pericardial effusion 23 (46%), pericardial calcification 6 (12%), and pericardial nodule 5 (10%). In 28 (56%) patients, only the pericardium was affected. In addition to the pericardium, eight (16%) patients had one other organ affected, and 11 (22%) patients had two additional organs affected. Two (4.5%) cases ended in demise.ConclusionAlthough rare, IgG4-RD can cause pericarditis, leading to pericardial thickening, effusion, constrictive pericarditis, or the formation of pericardial nodules. Treatment with corticosteroids or pericardiectomy has been associated with favorable outcomes.IntroductionImmunoglobulin G4-related disease (IgG4-RD) is an immune-mediated, fibroinflammatory condition that affects multiple organs in the body. It is a slowly progressing and often debilitating disease, with the potential to be fatal in some cases [1]. The condition was first suspected in the pancreas where a subset of autoimmune pancreatitis was associated with elevated levels of serum IgG4, now termed autoimmune pancreatitis type I [2]. The discovery that individuals with autoimmune pancreatitis also develop extra-pancreatic fibroinflammatory lesions containing abundant IgG4-bearing cells, in addition to histopathological features consistent with that in the pancreas, which include; dense lymphoplasmacytic infiltration, storiform fibrosis, and either obliterative or non-obliterative phlebitis, contributed to the establishment of the concept of IgG4-RD as a unique clinical entity in 2003 [1-3]. For decades, conditions such as Riedel thyroiditis, sclerosing cholangitis, Mikulicz’s syndrome, hypertrophic pachymeningitis, and retroperitoneal fibrosis were considered distinct entities. However, they are now classified within the spectrum of IgG4-RD, as they have been found to share similar histologic features and present concurrently in some patients [4].The worldwide prevalence and incidence of IgG4-RD are mostly underreported. Still, studies from Japan have revealed that the incidence of autoimmune pancreatitis increased from 0.8 to 3.1 cases per 100,000 people between 2007 and 2016, suggesting a swift rise in recognition of IgG4-RD within just a decade [4]. There is a higher prevalence among males, with the average age at diagnosis typically ranging from the fifth to sixth decade of life. However, classic presentations have also been documented in pediatric patients [1]. Cigarette smoking is the only well-documented modifiable risk factor associated with the development of IgG4-RD [5]. A genome-wide association study revealed that the FC-γ receptor IIb and HLA-DRB1 regions were associated with an increased susceptibility to IgG4-RD, indicating a potential genetic predisposition to its pathogenesis [6].The pathophysiology of IgG4-RD remains incompletely understood. However, several critical components have been identified, including the migration of activated B cells to the site of inflammation, where they facilitate the expansion and differentiation of T cells into CD4+ cytotoxic T lymphocytes (CTLs). These CD4+ CTLs subsequently induce apoptosis by releasing perforins and granzymes. In response, activated M2 macrophages clear the apoptotic cells while also contributing to the activation of fibroblasts. This activation is promoted through several mediators, including IFN-γ (interferon-gamma), TGF-β (transforming growth factor-beta), and IL-1 (interleukin-1) from CD4+ CTLs, along with PDGF (platelet-derived growth factor) from activated B cells, and various factors from macrophages. As fibroblasts become activated, they secrete extracellular matrix proteins, leading to tissue remodeling and fibrosis. Over time, the progressive expansion of the extracellular matrix and increased cell proliferation contribute to the development of tumor-like masses and the subsequent enlargement of affected organs, as observed in clinical settings [7].While IgG4-RD has been reported in multiple organs, this study is the first to comprehensively review cases where it affects the pericardium, leading to pericarditis.MethodsStudy designThe present systematic review was conducted per the guidelines outlined by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA).Literature searchA thorough systematic search was conducted across Scopus, PubMed, Web of Science, and Google Scholar databases to retrieve studies published from inception until March 1, 2025. The search employed the following keywords: “IgG4 OR IgG4RD OR immunoglobulin AND pericarditis OR tamponade OR pericardial OR pericardium OR serositis OR serosal”Eligibility criteriaThe inclusion criteria were restricted to English-language publications involving only human subjects, specifically case-control studies, cohort studies, cross-sectional studies, or case reports. Additionally, due to the limited number of studies on this topic, conference papers containing adequate information were also included.All age groups, both sexes, with confirmed pericarditis through a combination of clinical examination, ECG (electrocardiography), diagnostic imaging (including echocardiography, magnetic resonance imaging (MRI), computed tomography (CT), positron emission tomography (PET)), laboratory investigations, or histopathological examination of the pericardial tissue or fluid were included. Given the limited number of reports on this entity and a lack of standardized diagnostic criteria for IgG4-RD pericarditis, such as an established IgG4/IgG ratio or IgG4/high power field (HPF) in pericardial specimens or its necessity in the first place when other clues are suggestive of this disease, this review adopted an inclusive approach. With patients of either of the following criteria being included: 1) Patients with pericardial biopsy showing an IgG4/IgG ratio of >40% or reported as “increased”. 2) Patients with pericardial biopsy revealing IgG4/HPF of >10 or reported as “increased”. 3) Patients who had confirmed IgG4-RD from other organ biopsies through IgG4 staining, or diagnostic imaging suggestive of IgG4-RD, or pericardial biopsy with classic IgG4-RD histopathologic patterns, with elevated serum IgG4 levels, provided no other diagnosis was more likely.The exclusion criteria included studies with incomplete information about the patients or the method of diagnosis. Patients who were more likely to have pericarditis due to causes other than IgG4-RD. Studies from journals with inadequate peer review and questionable reliability were excluded [8].Study selectionThe screening process commenced with two independent researchers who systematically reviewed the titles and abstracts of all identified studies. Following this initial assessment, a comprehensive full-text evaluation was conducted based on predefined inclusion and exclusion criteria. Studies that satisfied these eligibility criteria were subsequently selected for inclusion. In instances where disagreements emerged between the two researchers, a third author was consulted to mediate and resolve conflicts through discussion and consensus.Data itemsData extraction was conducted using Microsoft Office Excel 2016. The following variables were collected for each study: first author’s name, year of publication, study design, country of origin, sample size, patient sex, age, past medical and surgical history, family history, presenting complaint, and duration of symptoms. Additionally, data regarding pericardial involvement were extracted, including the presence of pericardial thickening, constrictive physiology, pericardial calcification, and pericardial nodules. The presence or absence of pleural disease was also recorded.If available, findings from diagnostic imaging modalities such as chest radiography, echocardiography, CT, MRI, PET, and right heart catheterization were documented. Laboratory results, when reported, were extracted for C-reactive protein (CRP), Erythrocyte sedimentation rate (ESR), N-terminal pro-brain natriuretic peptide (NT-proBNP), serum IgG4 levels, serum IgG4/IgG ratio, and any other notable laboratory parameters.Furthermore, the number of organs affected by IgG4-RD, and the histopathological findings were collected. Treatment modalities, including both successful and unsuccessful interventions, were documented, along with follow-up duration and clinical outcomes.Data analysisThe data were analyzed using the Statistical Package for Social Sciences (SPSS) version 26.0, which facilitated the quantitative synthesis of the information. Relevant variables were displayed in summary tables, with categorical data represented by frequency and percentage, and quantitative data summarized using the mean and standard deviation.ResultsStudy selectionThe literature search yielded 87 studies from the databases. During the initial screening, one study was removed due to duplication, four for being in a non-English language, and four were closed access/unretrievable. The 78 studies remained for screening through titles and abstracts. Of these, eleven were excluded from the title and three from the abstract due to irrelevancy.During the full-text screening, two retrospective cohort studies were excluded even though they included patients with IgG4-RD causing pericarditis. As those studies also included patients with IgG4-RD affecting other organs without pericardial involvement. However, they did not provide specific details on the characteristics, diagnostic workup, or histopathological findings of IgG4-RD in the subset of patients with pericarditis. As a result, they did not meet the inclusion criteria for this systematic review. One study was excluded as there was insufficient information to diagnose IgG4-RD. Additionally, two other studies were excluded after the full-text screening because they did not report IgG4-RD as a cause of pericarditis. Letters to the editor and preprints were excluded, with six and one paper removed respectively. Two studies were excluded from journals with inadequate peer review. Ultimately a total of 50 studies were included in the current systematic review for analysis (Figure 1).Characteristics of the studiesOf the included studies, 40 (80%) were case reports, and ten (20%) were conference abstracts. Japan 22 (44%) and the United States of America 17 (34%) had the most publications, followed by Korea 3 (6%), the other studies were all from different countries (Table 1, Table 2, Table 3) [9-58].Table 1. Demographics and clinical presentations of patients.AuthorYearCountryStudy typeNo. casesAge (y)SexPresenting complaintDurationPMHPleural diseasePericardial manifestationsExtra-pericardial IgG4-RD organ involvementKhodabandeh et al. [9]2010USAP154MDyspneaN/ANoYesThickening, constrictive pericarditisNoHorie et al. [10]2012USAP176MDyspnea, peripheral edema24N/AYesThickening, constrictive pericarditisNoKabara et al. [11]2012JapanC169MPeripheral edema12N/AYesPericardial effusionNoSekiguchi et al. [12]2012USAC129FDyspnea, chest pain60N/AYesThickening, constrictive pericarditisPleural thickeningSekiguchi et al. [13]2012USAC176MDyspnea, peripheral edema24N/AYesThickening, constrictive pericarditisNoKassier et al. [14]2014USAP175MPeripheral edemaN/AN/ANoThickening, constrictive pericarditis, effusion, calcificationNoMorita et al. [15]2014JapanC160FReferred for cardiac tamponadeN/AN/ANoThickening, effusion, tamponadeLacrimal and parotid glands, mediastinal lymph nodesSeo et al. [16]2014KoreaC158MDyspnea, fatigue0.25CancerYesConstrictive pericarditisNoYanagi et al. [17]2014JapanC181MDyspnea, peripheral edema, anorexiaN/AHTNYesThickening, constrictive pericarditisNoMatsumiya et al. [18]2015JapanC150FChest pain, fever, fatigue1AsthmaYesThickeningMediastinal lymph nodesMori et al. [19]2015JapanC165MNausea, abdominal pain0.1DyslipidemiaNoThickeningPancreas, biliary systemSendo et al. [20]2015JapanC178FDyspneaN/AHTN, pulmonary tuberculosis, asthmaNoThickening, effusionPancreas, multiple lymph nodesHorie et al. [21]2016JapanC173MDyspnea2HTN, DMYesThickening, constrictive pericarditis, effusionNoHourai et al. [22]2016JapanC175MIncidental findingN/AHDYesThickening, effusionMediastinal lymph nodes, coronary arteryIbe et al. [23]2016JapanC172MDyspnea, weight loss1NoYesThickening, constrictive pericarditis, effusion, nodule on the pericardiumNoKondo et al. [24]2016JapanC178MPeripheral edema, elevated liver enzymes24N/AYesThickening, constrictive pericarditis,Pleural thickening/plaques, sclerosing cholangitisMoreno et al. [25]2016SpainC170MDyspnea12HTN, dyslipidemia, HD, COPD, CML, aortitisYesPericardial effusionAorta, bilateral renal sinus fatTerzic et al. [26]2017SerbiaC153MFatigue12N/ANoThickening, constrictive pericarditis, effusion, calcificationRetroperitoneumMatsuda et al. [27]2018JapanC170FBilateral lacrimal gland enlargement24N/ANoPericarditisCoronary artery, lacrimal glands, retroperitoneum, pancreas and right common iliac artery, ascending aortaSteiner et al. [28]2018USAP178MDyspnea, peripheral edema, ascitesN/AN/AYesThickening, constrictive pericarditis, calcification, pericardial massNoWeiss et al. [29]2018USAC183MIncidental findingN/ACancer, constrictive pericarditis, pericardial effusion, HDNoThickening, constrictive pericarditisNoArao et al. [30]2019JapanC164FAbdominal fulness1HTN, AsthmaNoPericardial effusionUreteral wallGorecka et al. [31]2019IrelandC153FWeight loss, chest pain, fatigue6NoYesThickening, effusionNoSly et al. [32]2019USAP137MChest painN/AN/ANoThickening, effusionNoTomoda et al. [33]2019JapanC172FDyspneaN/AN/ANoPericarditis, nodules on pericardiumMediastinal lymph nodesWang et al. [34]2019ChinaP180MDyspnea3N/AYesThickening, constrictive pericarditis, calcification.NoYassi et al. [35]2019USAC136MChest painN/ANoNoThickening, constrictive pericarditisNoMeier et al. [36]2020USAC178MAcute respiratory failureN/ARecurrent pericardial and pleural effusionYesPericardial effusionAorta, retroperitoneal fibrosisYamamoto et al. [37]2020JapanC175MIncidental findingN/ADM, HD, dementiaNoThickening, pericardial nodule, effusionNoYuriditsky et al. [38]2020USAC179MDyspneaN/AHD, recurrent pleural effusionYesThickening, constrictive pericarditis, pericardial calcificationNoCorona-Rodarte et al. [39]2021MexicoC144MCough, peripheral edema, dyspnea, weight loss, fever4N/AYesConstrictive pericarditis, effusionNoDoumen et al. [40]2021BelgiumC176FDyspnea, cough2DM, HTN, COPD, dyslipidemiaYesPericarditisNoFujita et al. [41]2021JapanC183MDyspnea, weight gain0.25N/AYesThickening, constrictive pericarditisNoMajid et al. [42]2022USAC154MDyspnea, peripheral edema, chest pain, fatigueN/AHTNNoThickening, constrictive pericarditisNoMaltes et al. [43]2022PortugalC168MPeripheral edema, ascitesN/AHDNoThickening, constrictive pericarditisNoOhman et al. [44]2022USAP151FJaundice, ascites, weight lossN/AAsthmaNoThickening, constrictive pericarditisOmentum, uterusGeorge et al. [45]2023USAP141MVomiting, weight loss, dyspnea12N/ANoThickening, constrictive pericarditisNoKawanami et al. [46]2023JapanC166MRefractory pericarditisN/AN/AYesThickening, effusion, pericardial noduleAortic root, coronary arteriesLildar et al. [47]2023USAP179MDyspneaN/ACancer, chronic pancreatitisNoPericardial effusionPancreas, multiple lymph nodesSaad et al. [48]2023EgyptC113FDyspnea, hemoptysis, fever, weight loss2N/AYesThickening, effusionLungsSugawara et al. [49]2023JapanC167FChest pain, palpitationN/ADM, AsthmaNoPericardial effusionSubmandibular glandWei et al. [50]2023JapanC182FChest pain, abdominal fullness8N/AYesPericardial effusionSubmandibular glands, pharyngeal tonsilsAn et al. [51]2024KoreaC166FDyspnea, peripheral edema0.5N/AYesThickening, constrictive pericarditis, effusionNoMiura et al. [52]2024JapanC172MIncidental findingN/AN/ANoThickening, effusionAorta, coronary artery, submandibular glandOkabe et al. [53]2024JapanC182MPeripheral edema, sialadenitis3DM, HD, idiopathic exophthalmosYesConstrictive pericarditis, calcificationSalivary glands, orbitOzgur et al. [54]2024USAC155MDyspnea, peripheral edema, hemoptysis, weight loss6DMYesThickening, constrictive pericarditisNoShimada et al. [55]2024JapanC172MScrotal edema, ascitesN/AHTNYesThickening, constrictive pericarditisAortaSon et al. [56]2024KoreaC177MAnorexia, fever3HTN, dyslipidemiaYesThickening, effusionNoThummala et al. [57]2024USAP151MDyspneaN/AHD, CKDNoThickening, constrictive pericarditisNoOno et al. [58]2025JapanC167MDyspnea, peripheral edema, anorexia6Liver dysfunctionYesThickening, constrictive pericarditisNoM: Male, F: Female, DM: Diabetes mellitus, HTN: Hypertension, CKD: Chronic liver disease, HD: Heart disease, COPD: Chronic obstructive lung disease, CML: Chronic myeloid leukemia, USA: United States of America, P: Conference abstracts, C: Case report, N/A: Not available.Table 2. Radiological, electrocardiography, and heart catheterization findings of the cases.AuthorX-rayEchocardiographyCTCardiac MRIPET-CTECGRight heart catheterizationKhodabandeh et al. [9]N/AConstrictive physiology, pericardial thickeningPericardial thickening, bilateral pleural effusionN/AN/AN/AConstrictive physiologyHorie et al. [10]Bilateral pleural effusionConstrictive physiologyN/ASuggestive of constrictive pericarditisN/AN/AConstrictive physiologyKabara et al. [11]CardiomegalyCollapsed left atrium, pleural effusionPericardial effusion, retroperitoneal fibrosisN/AN/AN/AN/ASekiguchi et al. [12]Bilateral lung opacitiesConstrictive physiologyPericardial thickening, bilateral pleural thickening, right-sided pleural effusionN/AN/AN/AN/ASekiguchi et al. [13]Bilateral pleural effusionConstrictive physiologyN/AConstrictive physiologyN/AN/AConstrictive physiologyKassier et al. [14]N/APericardial thickening, pericardial effusion, pericardial calcificationN/APericardial thickening, pericardial delayed hyperenhancementN/AAtrial flutterConstrictive physiologyMorita et al. [15]CardiomegalyPericardial thickeningPericardial thickeningN/AN/ANormal sinus rhythmN/ASeo et al. [16]Bilateral pleural effusion, cardiomegalyConstrictive physiology, pericardial effusionN/AN/APericardial effusionN/AN/AYanagi et al. [17]Bilateral pleural effusionPericardial thickening, constrictive physiologyPericardial thickeningConstrictive physiology, pericardial thickeningN/ASinus rhythm, low-voltage QRS complexesConstrictive physiologyMatsumiya et al. [18]NormalPericardial thickeningPericardial thickening, left-sided pleural effusion, mediastinal lymphadenopathyN/APatchy uptake in the pericardium, and a dense uptake in the mediastinal lymph nodeNormal sinus rhythmN/AMori et al. [19]NormalNormalPericardial thickening, pancreatic parenchyma enlargement, common bile duct wall thickeningN/AN/ANormal sinus rhythmN/ASendo et al. [20]CardiomegalyPericardial effusionPericardial effusion, lymphadenopathies in the mediastinum, para-aorta, abdominal cavity, and inguinal region. diffuse enlargement of the pancreas, and bilateral hydronephrosis.N/AN/AN/AN/AHorie et al. [21]Bilateral pleural effusion, cardiomegalyPericardial effusionN/AN/ALocalized uptake in the pericardiumN/AConstrictive physiologyHourai et al. [22]Cardiomegaly, bilateral pleural effusionN/APericardial thickening, pericardial effusion, and thickening of the perivascular regions of the abdominal aortaN/AEnhanced uptake in mediastinal lymph nodes, pericardium, and perivascular regions of the abdominal aorta and aortic wallN/AN/AIbe et al. [23]Bilateral pleural effusionConstrictive physiology, pericardial effusionN/AConstrictive physiology, pericardial thickening, pericardial effusion, enhancement of pericardiumN/AN/AConstrictive physiologyKondo et al. [24]N/AN/AN/AN/ABilateral pleural effusion, thickening of the pleuro-pericardial wall, and accumulation in the right pleuraN/AConstrictive physiologyMoreno et al. [25]N/APericardial effusionPericardial effusion, bilateral pleural effusion, aortitis, and bilateral obliteration of renal sinus fatN/AN/AN/AN/ATerzic et al. [26]CardiomegalyPericardial effusionPericardial effusion, retroperitoneal fibrosisN/AN/ASinus rhythm, low-voltage QRS complexesN/AMatsuda et al. [27]N/AN/ALeft circumflex artery wall thickeningN/AUptake in left ventricular wall, left circumflex artery wall, and ascending aorta. e findings suggested dacryoadenitis, retroperitoneal fibromatosis, pancreatic periarteritis, and right common iliac periarteritis.N/AN/ASteiner et al. [28]N/AConstrictive physiology, anterior pericardial massPericardial thickening, pericardial calcification, pericardial nodule, bilateral pleural effusionN/AN/AN/ANot definitive for constrictive physiologyWeiss et al. [29]N/AN/AN/AN/AN/AN/AN/AArao et al. [30]CardiomegalyPericardial effusionPericardial effusion, ureteral wall thickeningN/AN/ASinus rhythm, low-voltage QRS complexesN/AGorecka et al. [31]Bilateral pleural effusionPericardial effusion, mild impairment of left ventricular function and moderate mitral regurgitationN/APericardial thickening, and active inflammation of the pericardiumN/AN/AN/ASly et al. [32]N/AConstrictive physiology, pericardial effusionPericardial effusionN/AN/ADiffuse ST elevations and PR depression.Constrictive physiologyTomoda et al. [33]N/APericardial effusionPericardial thickening, mediastinal lymphadenopathyN/AN/AN/AN/AWang et al. [34]N/AN/APericardial thickening, bilateral pleural effusion, ascitesN/AN/AN/AConstrictive physiologyYassi et al. [35]N/AN/AN/AN/AN/AChanges consistent with acute pericarditisN/AMeier et al. [36]N/AN/APericardial effusion, right-sided pleural effusion, aortitis, pulmonary embolism, retroperitoneal fibrosis.N/AN/AN/AN/AYamamoto et al. [37]N/AN/APericardial thickening, pericardial nodules, and pericardial and paraphrenic lymph node enlargementPericardial thickening, pericardial effusion, with inhomogeneous gadolinium enhancementMetabolic activity in the pericardial nodular lesionsNormal sinus rhythmNormalYuriditsky et al. [38]N/AConstrictive physiologyPericardial thickening, right-sided pleural effusionConstrictive physiologyN/ASinus rhythm, incomplete right bundle branch block and a left anterior fascicular blockConstrictive physiologyCorona-Rodarte et al. [39]N/AConstrictive physiology, pericardial effusionPrevascular, and pretracheal mediastinal lymphadenopathies, bilateral pleural effusion, atelectasis, pericardial effusion with contrast enhancement of the pericardiumSuggestive of constrictive pericarditisN/AN/AN/ADoumen et al. [40]Bilateral pleural effusion, cardiomegalyPericardial effusionNormal after treatmentPericardial effusion, pericardial thickeningUnspecified pericardial uptakeSinus rhythm, incomplete right bundle branch blockN/AFujita et al. [41]Bilateral pleural effusion, cardiomegalyPericardial thickening, constrictive physiologyPericardial thickening, pericardial effusionAdhesion between pericardium and myocardiumN/ASinus rhythm, low-voltage QRS complexesConstrictive physiologyMajid et al. [42]N/AConstrictive physiology, pericardial effusionN/APericardial effusion, constrictive physiology, marked pericardial delayed enhancementN/AN/AN/AMaltes et al. [43]N/APericardial thickening, constrictive physiologyPericardial thickening, an anomalous pulmonary venous returnPericardial thickening with diffuse late gadolinium enhancementN/AN/AConstrictive physiologyOhman et al. [44]N/AConstrictive physiologyHepatomegaly, thickening of the uterus, and omentumConstrictive physiology, pericardial thickeningN/AN/AN/AGeorge et al. [45]N/APericardial thickening, and myocardial-pericardial tethering of left ventricle apical segmentsPericardial thickeningConstrictive physiologyN/AN/AConstrictive physiologyKawanami et al. [46]N/APericardial effusion, a hyperechoic lesion around the aortic root, and multiple nodules in the pericardiumPericardial thickening. contrast-enhancing nodules along the pericardium and soft tissue around the aortic root, coronary artery, and dorsal left atriumN/AFocal uptake consistent with the lesions detected by contrast-enhanced CTNormal sinus rhythmN/ALildar et al. [47]N/APericardial effusion with early diastolic RV collapse, suggestive of cardiac tamponadePancreatic calcification consistent with chronic pancreatitis and fluid localized to the tail suggesting acute uncomplicated pancreatitisN/AN/AElectrical alternansN/ASaad et al. [48]N/AN/APericardial thickening, pericardial effusion, left pleural basal thickening in addition to bilateral patchy areas of pulmonary interstitial thickening (consolidation) and ground glass veilingN/AN/AN/AN/ASugawara et al. [49]N/AN/APericardial effusionN/AUptake in the pericardium and submandibular glandSinus tachycardiaN/AWei et al. [50]N/APericardial effusionPericardial effusion, bilateral pleural effusionN/APericardial effusion corresponds to an increased area of uptake. Bilateral pharyngeal tonsil, submandibular gland, small lymph nodes in the right side of sternal bone and mediastinum and the wall of ascending aortaSinus rhythm, low T-waveN/AAn et al. [51]N/AConstrictive physiology, pericardial effusionPericardial thickening, pericardial effusion, and left-sided pleural effusionsN/APatchy uptake in the pericardiumSinus rhythm, low-voltage QRS complexesN/AMiura et al. [52]N/AN/APericardial thickening, pericardial effusionN/AN/AN/AN/AOkabe et al. [53]N/AConstrictive physiologyPericardial calcificationN/AN/AAtrial fibrillationConstrictive physiologyOzgur et al. [54]Right-sided pleural effusion.Constrictive physiologyN/APericardial thickening with increased enhancement on delayed myocardial enhancementN/ANormal sinus rhythmConstrictive physiologyShimada et al. [55]Cardiomegaly, blunted left costophrenic angleConstrictive physiologyPericardial thickening, DeBakey type II aortic dissectionN/AN/ANormal sinus rhythmN/ASon et al. [56]Cardiomegaly, blunted left costophrenic angleConstrictive physiology, pericardial effusion, fibrinous strandsPericardial thickening, pericardial effusion, and bilateral pleural effusionsN/ADiffusely increased uptake in the pericardiumSinus tachycardiaN/AThummala et al. [57]N/AN/AN/AConstrictive physiology, pericardial thickeningN/AN/AConstrictive physiologyOno et al. [58]Cardiomegaly, blunted right costophrenic anglePericardial thickening, constrictive physiologyRight-sided pleural effusion, pericardial thickeningN/AN/ANormal sinus rhythm, prominent P wavesConstrictive physiologyCT: Computed tomography, MRI: Magnetic resonance imaging, PET: Positron emission tomography.Table 3. Laboratory and histopathological findings, treatment strategies, and outcomes.AuthorSerum IgG4 (mg/dl)Serum IgG4/IgGPericardial tissue IgG4/IgGPericardial IgG4/HPFHistopathology sample locationUnsuccessful initial treatmentSuccessful treatmentMaintenance treatmentFollow-up (months)OutcomeKhodabandeh et al. [9]150N/AN/AN/APericardiumThoracentesisPericardiectomyN/AN/AClinically improvedHorie et al. [10]N/AN/A34%33PericardiumDiuretics, after-load reducing agent, paracenteses and thoracentesesPericardiectomyNo24RemissionKabara et al. [11]40823%N/AN/AN/ANoPrednisolonePrednisolone1RemissionSekiguchi et al. [12]136NoN/AN/APleuraNoPrednisonePrednisone for 6 months then stopped12RemissionSekiguchi et al. [13]N/AN/A34%33PericardiumParacentesis, Thoracocentesis, diuretics, afterload-reducing agentsPericardiectomyNo24RemissionKassier et al. [14]62N/A"Increased""Increased"PericardiumN/AN/AN/AN/AN/AMorita et al. [15]180087%"Increased""Increased"PericardiumPericardiocentesisPrednisolonePrednisolone18RemissionSeo et al. [16]15010.18%5%30PericardiumFurosemide, spironolactone, pericardial drainagePericardiectomyPrednisoloneN/ARemissionYanagi et al. [17]196No68%24PericardiumNoPericardiectomy and pericardiotomy (Waffle procedure)Prednisolone1.25RemissionMatsumiya et al. [18]428N/ANoN/AMediastinal biopsyNoPrednisoloneN/A28RemissionMori et al. [19]637N/AN/AN/ANoNoPrednisolonePrednisolone24RemissionSendo et al. [20]92124.10%51%86Inguinal lymph node and pericardiumPericardiocentesisPericardial drainage, prednisoloneN/AN/AClinically improvedHorie et al. [21]1227%42%N/APericardiumPericardiocentesis, furosemide, tolvaptan, dobutaminePrednisolonePrednisolone2RemissionHourai et al. [22]62518%N/AN/AMediastinal lymph nodeNoCorticosteroidCorticosteroidN/ARemissionIbe et al. [23]1778.70%>50%"Increased"PericardiumN/AN/AN/AN/AN/AKondo et al. [24]700N/A50%30Pericardium and pleuraPrednisolonePericardiectomyN/AN/AClinically improvedMoreno et al. [25]437N/AN/AN/ANoNoMethylprednisolonePrednisone, cyclophosphamide10RemissionTerzic et al. [26]163N/AN/AN/APericardiumIbuprofen, ceftriaxone, prednisolonePericardiectomy, prednisolone, azathioprinePrednisolone, azathioprine48Several recurrencesMatsuda et al. [27]78538.60%NoN/ALacrimal glandsNoPrednisolonePrednisolone2RemissionSteiner et al. [28]205No"Increased""Increased"PericardiumDiuretics, anti-inflammatory drugs, thoracentesisPericardiectomyN/AN/AClinically improvedWeiss et al. [29]N/AN/ANo>50Pericardial biopsy from 5 years agoNoPericardiectomyNo60RemissionArao et al. [30]96246.70%NoN/ANoNoPrednisolonePrednisolone24RemissionGorecka et al. [31]N/AN/A>40%N/APericardiumNoCD 20 monoclonal antibodyCD 20 monoclonal antibodyN/ARemissionSly et al. [32]ElevatedNo"Increased""Increased"PericardiumAspirin, colchicine, pericardiocentesisPericardiectomyPrednisoneN/ARemissionTomoda et al. [33]358056.10%NoN/AMediastinal lymph nodesNoPrednisolonePrednisolone12RemissionWang et al. [34]N/AN/ANo"Increased"PericardiumNoPericardiotomy, prednisonePrednisone60RemissionYassi et al. [35]ElevatedNo65%65PericardiumAspirin, colchicine, vancomycin, cefazolin, corticosteroid, ibuprofenPericardial windowCorticosteroid3RecurrenceMeier et al. [36]N/AN/AN/A4Pericardium and pleurathoracoscopic pleurodesis and tunneled right pleural catheter, pericardiotomyCorticosteroid, rituximabCorticosteroid, rituximabN/AClinically improvedYamamoto et al. [37]212No51%29PericardiumNoPrednisonePrednisolone6RemissionYuriditsky et al. [38]30610.70%N/A"Few"Pericardium and pleuraPrednisone, diureticsPericardiectomyCorticosteroid2RemissionCorona-Rodarte et al. [39]55N/A>40%N/APericardiumAnti-tuberculous antibiotics, corticosteroid. Then after 1 month done pericardiectomy, ceftriaxone, vancomycinNoN/A1DeadDoumen et al. [40]17915.70%> 80%50PericardiumPericardiocentesis, pleural drainage, Colchicine + NSAIDPericardiectomyNo8RemissionFujita et al. [41]165No50%"Increased"PericardiumDiuretics, dobutamine, and non-invasive positive pressure ventilation, pericardial drainagePericardiectomyNo6RemissionMajid et al. [42]N/AN/A>30%N/APericardiumSteroid taper, colchicine and ibuprofenPericardiectomyN/AN/AClinically improvedMaltes et al. [43]N/AN/AN/A>20PericardiumNoPericardiectomy and surgical correction of anomalous pulmonary venous returnCorticosteroidN/AClinically improvedOhman et al. [44]ElevatedNoNoN/AOmental biopsyN/AN/ACorticosteroidN/AN/AGeorge et al. [45]123N/A>40%>30PericardiumNoPericardiectomy, prednisone, azathioprinePrednisone, azathioprine2RemissionKawanami et al. [46]415N/A"Increased"N/APericardiumNSAID, colchicinePrednisoloneN/A0.5RemissionLildar et al. [47]422N/AN/AN/ANoN/AN/AN/AN/AN/ASaad et al. [48]1686.40%No"Increased"PericardiumPericardiocentesis, pericardiotomyNoPrednisone, azathioprine, mycophenolate mofetil30Dead, massive hemoptysisSugawara et al. [49]228159.20%N/AN/ASubmandibular glandNoPericardial drainage, prednisoloneN/A12RemissionWei et al. [50]140081.40%N/AN/ASubmandibular glandFurosemide, spironolactoneMethylprednisolone, mycophenolate mofetilPrednisone12RemissionAn et al. [51]2550N/A>20%>50PericardiumNoprednisolone, colchicine, furosemidePrednisolone, colchicine for 3 months, then only prednisolone24RemissionMiura et al. [52]2270N/AN/AN/ASubmandibular glandNoCorticosteroidCorticosteroid12RemissionOkabe et al. [53]1168No40%10Minor salivary gland, PericardiumDiuretics, beta blockerPericardiectomy, waffle procedure, corticosteroidRituximab18Remission (improved exophthalmos)Ozgur et al. [54]1216NoNoN/APericardiumNoPericardiectomyN/A2RemissionShimada et al. [55]263NoNoN/AAortic biopsyDiuretics, anti-hypertensive drugsAscending aortic replacement, pericardiotomy followed by adhesion debridementDiuretic and prednisolone for 6 months, then stopped12RemissionSon et al. [56]234No50%>50PericardiumN/AN/AN/AN/AN/AThummala et al. [57]ElevatedNoNo"Increased"PericardiumN/AN/AN/AN/AN/AOno et al. [58]679N/A<7070PericardiumDiureticsPericardiectomyNo36RemissionPatient characteristicsA total of 50 patients were included in the study with a mean age of 64.86±15.79 years. There were 36 (72%) males. The past medical histories of 29 patients were provided which included hypertension 9 (31%), heart disease 8 (27.6%), and diabetes mellitus 6 (20.7%). Only two (4%) patients were previously diagnosed with IgG4-RD and one (2%) patient was suspected but not confirmed. No (0%) family history of IgG4-RD was reported in the included studies. The most common symptoms of patients included dyspnea 27 (54%), peripheral edema 16 (32%), chest pain 9 (18%), and weight loss 7 (14%). The mean duration of the presenting complaint was provided in 27 patients which was 9.4 months (Table 4).Table 4. Patient demographics and clinical features.VariablesNumber (%)Age (mean ± SD)64.86±15.79Sex Male36 (72) Female14 (28)Past medical histories (29) HTN9 (31) HD8 (27.6) DM6 (20.7) Dyslipidemia4 (13.8) Asthma4 (13.8) Malignancy3 (10.3) COPD2 (6.9) Pericardial effusion2 (6.9) Pleural effusion2 (6.9) Chronic pancreatitis1 (3.4) Chronic kidney disease1 (3.4) Aortitis1 (3.4) Idiopathic exophthalmos1 (3.4) Liver dysfunction1 (3.4) Pulmonary tuberculosis1 (3.4) Dementia1 (3.4)Presenting symptoms (50) Dyspnea27 (54) Peripheral edema16 (32) Chest pain9 (18) Weight loss7 (14) Fatigue5 (10) Fever4 (8%) Ascites4 (8%) Anorexia3 (6%) Cough2 (4%) Hemoptysis2 (4%) Nausea and Vomiting2 (4%) Abdominal fullness2 (4%) Jaundice1 (2%) Abdominal pain1 (2%) Palpitation1 (2%) Weight gain1 (2%) Sialadenitis1 (2%) Lacrimal gland enlargement1 (2%) Referred for cardiac tamponade1 (2%) Refractory pericarditis1 (2%) Elevated liver enzymes1 (2%) Incidental finding4 (8%)Pericardial manifestations (50) Pericarditis50 (100) Pericardial thickening37 (74) Constrictive pericarditis28 (56) Pericardial effusion23 (46) Pericardial calcification6 (12) Pericardial nodule5 (10)Pleural disease (50) Yes30 (60) No20 (40)Number of organs affected (50)Isolated pericardial involvement28 (56)Pericardium and one other organ8 (16)Pericardium and two other organs11 (22)Pericardium and three other organs2 (4)Pericardium and six other organs1 (2)Extra-pericardial IgG4-RD organ involvement (50)Aorta6 (12)Lymph nodes6 (12)Pancreas4 (8)Coronary artery4 (8)Retroperitoneum3 (6)Submandibular glands3 (6)Biliary system2 (4)Lacrimal gland2 (4)Pleural tissue2 (4)Right common iliac artery1 (2)Renal sinus fat1 (2)Lungs1 (2)Salivary gland1 (2)Orbit1 (2)Omentum1 (2)Uterus1 (2)Parotid gland1 (2)Pharyngeal tonsils1 (2)Ureteral wall1 (2)* The number in parentheses indicates the number of patients for whom information was provided.Pericardial involvementAll patients had pericarditis but with different associated pericardial involvements including pericardial thickening 37 (74%), constrictive pericarditis 28 (56%), and pericardial effusion 23 (46%) (Table 4).ECG findingsThe most common ECG findings were sinus rhythm 7 (30.4%), and sinus rhythm with low voltage QRS complexes 5 (21.7%) (Table 5).Table 5. Imaging and ECG characteristics of the patients.VariablesNumber (%)X-ray findings (22) *Bilateral pleural effusion10 (45.5)Cardiomegaly13 (59.1)Unilateral pleural effusion4 (18.2)Normal2 (9.1)Bilateral lung opacities1 (4.5)Transthoracic echocardiography (38)Constrictive physiology21 (55.3)Pericardial thickening9 (23.7)Pericardial effusion19 (50)Pericardial calcification1 (2.6)Pericardial mass1 (2.6)Fibrinous strands1 (2.6)Cardiac tamponade1 (2.6)Multiple pericardial nodules1 (2.6)Myocardial-pericardial tethering of-left ventricle apical segments 1 (2.6)Collapsed left atrium1 (2.6)Moderate mitral regurgitation1 (2.6)Hyperechoic aortic root lesion1 (2.6)Normal1 (2.6)CT findings (37)Pericardial thickening22 (59.5)Pericardial effusion16 (43.2)Pericardial calcification2 (5.4)Pericardial nodule3 (8.1)Bilateral pleural effusion7 (18.9)Unilateral pleural effusion6 (16.2)Retroperitoneal fibrosis3 (8.1)Aorta enhancement3 (8.1)Coronary artery enhancement/thickening2 (5.4)Mediastinal lymphadenopathy5 (13.5)Pulmonary embolism1 (2.7)An anomalous pulmonary venous return1 (2.7)Bilateral renal sinus fat obliteration1 (2.7)Ascites1 (2.7)Pleural thickening2 (5.4)Aortic dissection1 (2.7)Thickening of the uterus1 (2.7)Thickening of omentum1 (2.7)Hepatomegaly1 (2.7)Bilateral pulmonary interstitial thickening1 (2.7)Pancreatic calcification1 (2.7)Enlargement of pancreas2 (5.4)Bile duct wall thickening1 (2.7)Contrast enhancement of-the pericardium, and atelectasis 1 (2.7)Abdominal aorta perivascular area thickening1 (2.7)Abdominal lymphadenopathy1 (2.7)Bilateral hydronephrosis1 (2.7)Ureteral wall thickening1 (2.7)Normal1 (2.7)Cardiac MRI findings (17)Constrictive physiology11 (64.7)Pericardial thickening10 (58.8)Pericardial effusion4 (23.5)Pericardial enhancement10 (58.8)PET scan findings (13)Focal pericardial 18F-FDG uptake7 (53.8)Diffuse pericardial 18F-FDG uptake3 (14.3)Unspecified pericardial uptake3 (14.3)Uptake in other organs6 (46.1)ECG findings (23)Normal sinus rhythm7 (30.4)Sinus rhythm, low voltage QRS complexes5 (21.7)Sinus tachycardia2 (8.7)Atrial fibrillation1 (4.3)Atrial flutter1 (4.3)Normal sinus rhythm, prominent P waves1(4.3)Changes consistent with acute pericarditis1 (4.3)Diffuse ST elevations and PR depression.1 (4.3)Electrical alternans1 (4.3)Sinus rhythm, incomplete rightbundle branch block 1 (4.3)Sinus rhythm, incomplete right bundle-branch block and a left anterior fascicular block 1 (4.3)Sinus rhythm, low T-wave1 (4.3)* The number in parentheses indicates the number of patients for whom information was provided.Echocardiography findingsTransthoracic echocardiography was done in 38 individuals and revealed constrictive physiology, pericardial effusion, and pericardial thickening in 21 (55.3%), 19 (50%), and 9 (23.7%) patients respectively (Table 5). The ejection fraction was stated in 16 individuals which was normal in 10 (62.5%) and below the normal range in 6 (37.5%).X-ray findingsChest x-ray was performed in 22 patients which revealed bilateral pleural effusion in nine (40.9%) of them, and cardiomegaly in 13 (59.1%) patients (Table 5).CT findingsComputed tomography was conducted in 37 patients. Pericardial thickening and pericardial effusion were detected on CT among 22 (59.5%), and 16 (43.2%) patients respectively. Involvement of organs other than the pericardium included the following: retroperitoneal fibrosis 3 (8.1%), enlargement of the pancreas 2 (5.4%), bile duct thickening 1 (2.7%), mediastinal lymphadenopathy 5 (13.5%), and enhancement of the aorta 3 (8.1%) (Table 5).Cardiac MRI findingsA cardiac MRI that was performed on 17 individuals, revealed constrictive physiology 11 (64.7%), pericardial thickening 10 (58.8%), and pericardial enhancement 10 (58.8%) among the patients (Table 5).PET-CT scan findingsPositron emission tomography-CT was performed in 13 patients. Focal pericardial uptake of FDG was present in seven (53.8%) patients, and diffuse uptake in three (14.3%). Involvement of other organs was shown in six individuals (Table 5).Right heart catheterization findingsRight heart catheterization was performed in 20 patients, revealing constrictive physiology in 18 (90%) individuals. One (5%) patient had no definitive evidence of constrictive physiology, while another (5%) had normal findings.Laboratory findingsSerum IgG4 levels were reported in 42 patients with their levels being elevated (IgG4> 135mg/dl) in 38 (90.5%) individuals. The exact value of serum IgG4 was given in 38 individuals with a mean of 703.9 mg/dl ± 813.8. The serum ratio of IgG4/IgG was reported in 15 cases with a mean of 32.9% (6.4%-87%).C-reactive protein was measured in 24 patients, with 19 (79.2%) patients showing elevated levels. The exact value of CRP was reported in 18 individuals with a mean of 61 mg/L.NT-proBNP was reported in four patients with a mean of 782.45 pg/ml (223 - 15252 pg/ml). and BNP was reported in five patients with a mean of 228.75 pg/ml (10 - 649 pg/ml).Organs Affected by IgG4-RDIn 28 (56%) patients, only the pericardium was affected. In addition to the pericardium, eight (16%) patients had one other organ affected, eleven (22%) patients had two additional organs affected, two (4%) patients had three additional organs affected, and one (2%) patient had six other organs affected. The organs that are affected are summarized (Table 4).Diagnosis of IgG4-RD pericarditisPericardial tissue IgG4/IgGPericardial IgG4 staining was performed in 32 patients. Of these, 25 studies reported the pericardial IgG4/IgG ratio. In 15 (60%) cases, the IgG4/IgG ratio was greater than 40. Five (20%) cases reported an "increased" ratio, although the specific value was not provided. Regarding the number of IgG4/HPF. It was reported in 27 cases of which 25 (92.6%) had more than 10/HPF. These findings along with the combination of IgG4/IgG ratio and IgG4/HPF are summarized (Table 6).Table 6. Pericardial IgG4 histopathologic findings, and diagnostic approaches.VariablesNumber (%)Pericardial tissue IgG4/IgG ratio (25) *IgG4/IgG >40%15 (60)IgG4/IgG <40%5 (20)“increased”5 (20)Pericardial IgG4+ cells/ HPF (27)1-9/HPF2 (7.4)10-19/HPF1 (3.7)20-29/HPF3 (11.1)30-39/HPF5 (18.5)40-49/HPF0 (0)50>/HPF7 (25.9)“Increased”9 (33.3)Diagnostics for patients with IgG4 staining (32)Pericardial IgG4/IgG ratio> 40%/ “increased” or IgG4/HPF>10/ “increased”29 (90.6)Pericardial IgG4/IgG ratio> 40%/ “increased” and IgG4/HPF>10/ “increased”16 (50)Neither3 (9.4)Methods of diagnosis in those who did not fulfil the above criteria (21)submandibular gland IgG4 staining + CT pericardial finding + increased pericardial uptake on FDG-PETCT + elevated serum IgG42 (9.5)Submandibular gland IgG4 staining + CT pericardial findings + elevated serum IgG41 (4.8)lacrimal glands IgG4 staining + increased pericardial uptake on FDG-PETCT + elevated serum IgG41 (4.8)mediastinal lymph node IgG4 staining + CT pericardial finding + increased pericardial uptake on FDG-PETCT + elevated serum IgG41 (4.8)mediastinal lymph node IgG4 staining + CT pericardial findings + elevated serum IgG41 (4.8)mediastinal biopsy IgG-4 staining + CT pericardial findings + increased pericardial uptake on FDG-PETCT + elevated serum IgG41 (4.8)aortic biopsy IgG4 staining + CT pericardial findings + elevated serum IgG41 (4.8)pleural biopsy IgG4 staining + CT pericardial findings + elevated serum IgG41 (4.8)Omental biopsy IgG4 staining + elevated serum IgG41 (4.8)Pericardial biopsy + Cardiac MRI findings + elevated serum IgG4.1 (4.8)Pericardial biopsy + CT pericardial finding + elevated serum IgG41 (4.8)CT retroperitoneum fibrosis + CT pericardial findings + Pericardial biopsy + elevated serum IgG41 (4.8)CT aortitis and bilateral obliteration of renal sinus fat + CT pericardial findings + elevated serum IgG41 (4.8)CT retroperitoneal fibrosis and aortitis + pericardial biopsy after steroid therapy1 (4.8)Pericardial and pleural biopsy + elevated serum IgG41 (4.8)Pericardial biopsy findings + pericardial >30% IgG4- staining + Cardiac MRI findings 1 (4.8)CT ureteral wall thickening + pericardial effusion + elevated serum IgG41 (4.8)CT chronic pancreatitis + pericardial effusion + elevated serum IgG41 (4.8)CT pericardial fluid analysis + CT retroperitoneal fibrosis + elevated pericardial fluid IgG4 cells + elevated serum IgG41 (4.8)CT pericardial finding+ CT pancreatic and biliary system findings + elevated serum IgG41 (4.8)* The number in parentheses indicates the number of patients for whom information was provided.Methods of diagnosing IgG4 in patients without pericardial biopsy. In 21 patients who either did not undergo IgG4 staining on their pericardial biopsy or did not have a pericardial biopsy performed, the diagnosis was supported by evidence from biopsies of other organs, elevated serum IgG4 levels, and diagnostic imaging. These findings were consistent with IgG4-related disease as the most likely diagnosis, with no other condition being as probable (Table 6).Therapeutic approaches and OutcomesThe initial unsuccessful, successful, and maintenance treatment interventions are summarized (Table 7). The outcomes of 44 patients were reported. Remission or clinical improvement was achieved in 40 (90.1%) individuals, recurrence in two (4.5%), and death in two (4.5%) patients. The follow-up period was specified in 33 cases with a mean of 16.3 months (0.5 - 60 months).Table 7. Therapeutic approaches of patients.VariablesNumber (%)Successful treatment approaches remission or initial clinical improvement (42) *Corticosteroid alone14 (33.3)Corticosteroid + azathioprine + pericardiectomy2 (4.8)Corticosteroid + pericardiectomy + waffle procedure1 (2.4)Corticosteroid + pericardiotomy1 (2.4)Corticosteroid + pericardial drainage2 (4.8)Corticosteroid + mycophenolate mofetil1 (2.4)Corticosteroid + colchicine + furosemide1 (2.4)Corticosteroid + rituximab1 (2.4)Pericardiectomy14 (33.3)Pericardiectomy + pericardiotomy + waffle procedure1 (2.4)pericardiectomy and surgical correction of anomalous pulmonary venous return1 (2.4)Pericardial window1 (2.4)Pericardiotomy + ascending aortic replacement1 (2.4)CD-20 monoclonal antibody1 (2.4)Initial unsuccessful approaches (24)Corticosteroid + pericardiectomy + antibiotic1 (4.1)Corticosteroid + NSAID + colchicine + antibiotic1 (4.1)Corticosteroid + NSAID + antibiotic1 (4.1)Corticosteroid1 (4.1)Corticosteroid + diuretic1 (4.1)Corticosteroid + NSAID + colchicine1 (4.1)Pericardiocentesis + NSAID + colchicine2 (8.4)Pericardiocentesis + diuretic3 (12.5)Pericardiocentesis2 (8.4)Pericardiocentesis + pericardiotomy1 (4.1)Diuretics4 (16.7)Diuretics + NSAID + thoracentesis1 (4.1)Diuretic + beta blocker1 (4.1)NSAID + colchicine1 (4.1)Diuretics + thoracentesis1 (4.1)Thoracentesis1 (4.1)Pericardiotomy + thoracoscopic pleurodesis1 (4.1)Maintenance treatment (35)Corticosteroid21 (60)Corticosteroid + Azathioprine2 (5.7)Corticosteroid + Azathioprine + mycophenolate mofetil1 (2.9)Corticosteroid + cyclophosphamide1 (2.9)Corticosteroid + colchicine1 (2.9)Corticosteroid + CD 20 monoclonal antibody1 (2.9)CD 20 monoclonal antibody2 (5.7)Did not receive treatment6 (17)* The number in parentheses indicates the number of patients for whom information was provided.DiscussionThe tendency of IgG4-RD to affect certain organs has been recognized since the disease was first described. However, consistent patterns of clinical manifestations were not fully evaluated until recently. Currently, the disease is described as having four phenotypes based on the organs affected which include; pancreato-hepatobiliary disease (31%), retroperitoneal fibrosis with or without aortitis (24%), head and neck-limited disease (24%), and classic Mikulicz's syndrome with systemic involvement (22%). These phenotypes are observed to have different demographic characteristics and responses to treatment [4]. Unlike most autoimmune diseases, which predominantly affect females, IgG4-RD causing pericarditis primarily affects males, with an average onset in the sixth decade of life [59-61]. Additionally, most reported cases of IgG4-RD causing pericarditis are reported from Japan, a pattern similar to that observed in Takayasu arteritis. This geographic disparity suggests an underlying genetic predisposition, environmental triggers more commonly found in certain regions, or a higher level of physician awareness and diagnosis. Further research is needed to elucidate the reasons behind this observation [59, 62-65].In the present study, there were only three patients who reported a history of malignancy, but the follow-up period was not long enough to show if it could have been a premalignant condition and till now there is no definitive research determining the relationship between malignancy and IgG4-RD [1]. However, since the majority of retroperitoneal masses are malignant, and IgG4-RD can present as a mass in the retroperitoneum; it can be initially misdiagnosed as malignancy [66]. For instance, in a study by Zhou et al. which retrospectively examined a group of 63 patients, nearly 60% were initially suspected to have cancer which included lymphoma, pancreatic, colorectal, and gastric cancers, cholangiocarcinoma, and renal cell carcinoma. Alarmingly, some of these patients underwent invasive procedures such as nephrectomy, Whipple procedure, resecting and reconstructing the bile duct, and retroperitoneal mass removal [67].The most common clinical manifestations in patients were dyspnea, chest pain, and peripheral edema. However, there was significant variability in symptoms, reflecting the disease's ability to affect multiple organs throughout the body. This multisystem involvement contributes to diagnostic complexity. However, such challenges are not unique to IgG4-RD; for instance, Crohn’s disease exhibits extraintestinal manifestations in up to 25% of cases. The presence of non-caseating granulomatous inflammation aids in differentiating Crohn’s disease. Furthermore, Deshpande et al. have characterized IgG4-RD as analogous to sarcoidosis due to its propensity for multi-organ involvement, while also highlighting shared histopathologic features across affected tissues, Nevertheless, additional research is required to clarify the specific characteristics of the various organs involved in IgG4-RD [2, 68].Pericardial involvement in IgG4-RD presents with various manifestations, including pericardial effusion, calcification, nodule formation, and pericardial thickening. These differences may be attributed to the stage of disease at which pericarditis was investigated and diagnosed, as the duration of symptoms before clinical presentation is typically prolonged, often spanning months, due to the insidious nature of the condition. This variability could also reflect different phenotypes of IgG4-RD affecting the pericardium, resulting in distinct combinations of the aforementioned pericardial manifestations. However, further research is necessary to validate these hypotheses.The aorta, coronary artery, and retroperitoneum were the commonly involved “extra-pericardial” organ involvement in this review, which aligns with the manifestation of the retroperitoneal/aortitis phenotype as mentioned by Lanzillotta et al [4]. However, involvement of the pancreas, biliary system, submandibular, and lacrimal glands amongst others were still reported which belongs to the other phenotypes. Thus, it is challenging to determine whether pericarditis is specific to a particular phenotype of IgG4-RD or if it represents a shared manifestation across different phenotypes.In 2019, the American College of Rheumatology (ACR) and the European Alliance of Associations for Rheumatology (EULAR) collaboratively established classification criteria for IgG4-RD. To satisfy the classification criteria, patients must first show involvement (clinical, radiological, or histopathological) of a classical organ affected by IgG4-RD, which includes the pancreas, kidneys, orbits, aorta, retroperitoneum, major salivary glands, thyroid gland, lacrimal glands, biliary tree, meninges, and paravertebral soft tissue. Furthermore, it should not meet any of the exclusion criteria outlined in detail. However, not all published studies on IgG4-RD fulfill these criteria, nor the ones causing pericarditis were all in line with the classification criteria, which is a limitation of this systematic review, as it adopts a more inclusive approach. Nonetheless, these classification criteria are not intended for clinical diagnostic purposes but rather for ensuring the highest specificity and serve as a useful framework for clinicians when assessing the diagnosis [1, 69].In regards to laboratory investigations, the serum IgG4 concentration is the most prominent and frequently utilized biomarker for IgG4-RD. Notably, it is elevated in up to 90% of affected individuals. Consistent with this, the present study showed that 90.5% of the patients had elevated serum IgG4 levels. However, this prevalence is shown to vary significantly depending on the patient population studied, with some estimates suggesting elevations in as few as 50% of cases. Serum IgG4 levels can decrease significantly following treatment compared to pre-treatment levels. Although measuring serum IgG4 concentration is often essential for evaluating and managing IgG4-RD over time, its clinical utility should be interpreted within the broader context of the patient’s overall clinical presentation and disease characteristics. In addition, several other biomarkers are associated with disease activity and the extent of organ involvement. Among these, elevated eosinophil counts, increased serum IgG1 and IgE levels, and alterations in serum complement levels have been frequently observed. These markers, in conjunction with serum IgG4, provide valuable insights into disease progression and severity [1]. For example, Gorecka et al. reported increased eosinophil counts, while Matsumiya et al. identified significantly high IgE levels of 1765 IU/ml [18, 31]. Elevated IgE levels were also noted in several other cases of IgG4-RD pericarditis, all of whom had no prior history of allergic reactions [19, 37, 54]. Additionally, ESR was elevated in a subset of patients, as reported by Terzic et al., Moreno et al., and Wei et al [26, 25, 50]. However, the aforementioned biomarkers were not measured or reported in the majority of the included studies, limiting the ability to establish a clear association between them and IgG4-RD pericardial involvement.While Katz et al. indicated that elevated CRP levels are less commonly observed compared to ESR, high CRP levels were found in a considerable subset of patients with IgG4-RD pericarditis. However, its diagnostic value in IgG4-RD is not well elucidated as CRP can be increased in a myriad of conditions including, immune-mediated diseases, malignancy, and COVID-19 among other communicable diseases [1, 70-73].The cutoff value of IgG4/HPF for diagnostic purposes varies significantly across different tissues, as reported by Dashpande et al. For biopsy specimens of the kidney and pancreas, it is often greater than 10 IgG4/HPF, whereas in aorta or pleura specimens, it may reach as high as 50 IgG4/HPF. However, there is no established diagnostic cutoff for pericardial tissue, and further research is needed to determine this value. Additionally, given the invasive nature of pericardial biopsy, it may be necessary to rely on biopsies from other sites or diagnostic imaging to reach a diagnosis in clinical practice. Some researchers have suggested a cutoff value of 40% for the IgG4/IgG plasma cell ratio as a general threshold across various organ tissues. While histopathology is crucial for diagnosis, it is important to recognize its limitations. Specifically, sampling errors may result in the absence of all classic histopathological features in certain patients. This is particularly true when small biopsy samples are obtained through CT-guided techniques, as opposed to larger specimens obtained through surgical resection. Such limitations may impact the diagnostic yield of using the IgG4/IgG ratio to assess pericarditis in IgG4-RD. For instance, in the current study, only half of the cases reported an IgG4/IgG ratio for pericardial tissue, with 80% of these showing elevated levels. Nevertheless, IgG4-RD was still considered the most likely cause of pericarditis in all the included patients by relying on other diagnostic methods. If a more stringent inclusion criterion had been applied in this review, a higher specificity might have been achieved. Nonetheless, we believe this study highlights an underreported and often overlooked cause of pericarditis, with histopathological examination being infeasible clinically in most cases due to the risk-benefit ratio [2]. The reported studies relied on several diagnostic imaging methods, for instance, Meier et al. reported that CT showed retroperitoneal fibrosis along with aortitis and the pericardial findings which hinted at the diagnosis of IgG4-RD [36]. Furthermore, Matsuda et al. employed PET scanning, which revealed dacryoadenitis, retroperitoneal fibromatosis, pancreatic periarteritis, and periarteritis of the right common iliac artery, along with uptake in the aorta and coronary artery [27]. The current study revealed the pattern of pericardial uptake on the PET scan varied, ranging from focal to diffuse, potentially indicating different phenotypes of IgG4-RD causing pericarditis or different stages of the same phenotype.An intriguing case study by Weiss et al. highlights the underdiagnosis of IgG4 as a cause of pericarditis and demonstrates how easily it can be overlooked if there is not a high index of suspicion. The authors reported an 84-year-old man with a history of constrictive pericarditis, for which he had undergone pericardiectomy. However, five years later, the patient presented with an enlarged aorta and pulmonary consolidation. Upon staining the five-year-old pericardial biopsy for IgG4, the results showed an IgG4/HPF count greater than 50. This led to a retrospective diagnosis of constrictive pericarditis due to IgG4-RD [29].Regarding therapeutic approaches, there was significant variability in treatment combinations for IgG4-RD pericarditis, underscoring the absence of a consensus on managing this condition. Treatment strategies ranged from conservative approaches, with most patients responding well to corticosteroids, to more invasive interventions such as pericardiectomy, which was deemed necessary in a substantial number of patients to achieve clinical improvement, particularly when constrictive physiology was confirmed through right heart catheterization. Maintenance treatment included corticosteroids and other immunosuppressive treatments such as azathioprine, cyclophosphamide, and rituximab. Clinical improvement and remission were achieved in most cases; however, recurrences were still reported in this review. Two patients died, one of whom was reported by Sad et al. In this case, a 13-year-old girl was treated with corticosteroids, azathioprine, mycophenolate mofetil, and rituximab for maintenance to prevent relapses. Unfortunately, these efforts were unsuccessful, as the patient experienced several recurrences and ultimately passed away due to massive hemoptysis, resulting from pleuropericardial and lung involvement of IgG4-RD [48]. In the case reported by Corona-Rodarte et al., a 44-year-old man was undergoing maintenance treatment with corticosteroids for a confirmed diagnosis of IgG4 pericarditis. The patient later presented with dyspnea and fever where his condition worsened, and blood cultures revealed the presence of non-typhoidal Salmonella group D. Subsequently, he developed septic shock and passed away [39].Even though pericardiectomy was performed in a substantial number of patients, this may be due to the fact that patients who do not respond to non-steroidal anti-inflammatory drugs (NSAIDs) and colchicine for idiopathic pericarditis are typically treated with corticosteroids and are then diagnosed with idiopathic pericarditis [74,75]. Among these patients, those who respond to corticosteroids may actually have IgG4-RD as the underlying cause. However, they may not undergo extensive diagnostic workup to suspect or confirm IgG4-RD. As a result, those who undergo more extensive diagnostic methods are more likely to be diagnosed with this condition, potentially influencing the current available data.One of the limitations of this systematic review lies in the quality of the case reports, which often exhibit inconsistent reporting of patients' medical histories, medication dosages, and outcomes. In some cases, the focus was solely on the diagnosis of the condition, with no follow-up on treatment results. Additionally, not all patients underwent pericardial IgG4 staining, and in those that did, the IgG4/IgG ratio and IgG4/HPF were not consistently reported, or a specific number was not provided, with some cases merely referring to the levels as "increased." However, a specific cutoff for IgG4 in the pericardium has yet to be agreed upon. Furthermore, serum IgG4 and other biomarkers associated with IgG4-RD were either not performed or not reported in the cases, nor were post-treatment levels of these markers included. Therefore, we strongly encourage the reporting of more detailed case studies, as well as the possibility of a retrospective study on pericardial biopsies to assess the sensitivity and specificity of IgG4 levels in pericardial tissues.ConclusionRecognizing IgG4-RD as a potential cause of pericarditis is crucial, as it is often overlooked. It can result in pericardial thickening, pericardial effusion, constrictive pericarditis, and pericardial nodule formation. Corticosteroids and pericardiectomy may result in good outcomes.DeclarationsConflicts of interest: The authors have no conflicts of interest to disclose.Ethical approval: Not applicable.Patient consent (participation and publication): Not applicable.Funding: The present study received no financial support.Acknowledgements: None to be declared.Authors' contributions: DH was involved in the literature review, study design, and writing of the manuscript. SAB, AM, AG, MAR, MA, KG, GS, RK, and MS were major contributors to the study's conception and involved in the literature review, the study's design, the critical revision of the manuscript. DH and AG confirm the authenticity of all the raw data. All authors have read and approved the final version of the manuscript.Use of AI: ChatGPT-4.0 was used to assist in language editing and improving the clarity of the manuscript. All content was reviewed and verified by the authors. Authors are fully responsible for the entire content of their manuscript.Data availability statement: Not applicable.